Strategi Implementasi PSAK 109 Dalam Peningkatan Akuntabilitas dan Transparansi Pelaporan Zakat - zainal potton (Jurnal Ilmiah Ekonomi Islam, 2023)
Abstract Institutions that conduct zakat are required to keep accurate books of account and be ready to be audited by a public accountant. Amil zakat financial statements will have problems being audited if the zakat institution has not implemented zakat accounting. In fact, an audit is one of the most crucial steps to increase public trust in zakat management organizations. Where PSAK 109 concerning zakat, infaq, and alms is obligatory to become a guideline for financial reporting for zakat, infaq, and alms institutions. The purpose of this study is how PSAK 109 Implementation Strategy in Improving the Accountability and Transparency of Zakat Reporting. The research method used is a qualitative descriptive approach. The techniques used to collect research data included observation, documentation, and interviews with informants from the finance, collection, and distribution sections of BAZNAS Enrekang Regency. The data analysis technique used was the method of triangulation of data interview documentation, observation and data reduction were used followed by drawing conclusions. The results of the study show that BAZNAS of Enrekang Regency has implemented PSAK 109, kept records with accountability and presented transparent financial reports. Keywords: BAZNAS, Accountability, Transparency, Financial Statements